2023
DOI: 10.3390/ijms241210048
|View full text |Cite
|
Sign up to set email alerts
|

CSF Markers of Oxidative Stress Are Associated with Brain Atrophy and Iron Accumulation in a 2-Year Longitudinal Cohort of Early MS

Andrea Burgetova,
Petr Dusek,
Tomas Uher
et al.

Abstract: In this prospective longitudinal study, we quantified regional brain volume and susceptibility changes during the first two years after the diagnosis of multiple sclerosis (MS) and identified their association with cerebrospinal fluid (CSF) markers at baseline. Seventy patients underwent MRI (T1 and susceptibility weighted images processed to quantitative susceptibility maps, QSM) with neurological examination at the diagnosis and after two years. In CSF obtained at baseline, the levels of oxidative stress, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Table S1 summarizes the results of studies related to markers of oxidative stress in the CSF from MS patients compared to controls [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. Most of these studies found increased CSF levels of markers of lipid peroxidation, such as malonyl-dialdehyde, hydroxyalkenals, diene conjugates, 4-hydroxy-nonenal, oxidized phosphatidylcholine, and isoprostanes in patients diagnosed with MS compared to controls [ 13 , 32 , 33 , 34 , 35 , 37 , 38 , 39 , 40 , 45 , 46 , 47 ], with some exceptions [ 36 ]. CSF levels of certain prostaglandins were increased in patients with MS in most studies [ 35 ,…”
Section: Oxidative Stress Markers In Patients With Multiple Sclerosismentioning
confidence: 99%
See 2 more Smart Citations

Oxidative Stress Markers in Multiple Sclerosis

Jiménez-Jiménez,
Alonso-Navarro,
Salgado-Cámara
et al. 2024
IJMS
“…Table S1 summarizes the results of studies related to markers of oxidative stress in the CSF from MS patients compared to controls [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. Most of these studies found increased CSF levels of markers of lipid peroxidation, such as malonyl-dialdehyde, hydroxyalkenals, diene conjugates, 4-hydroxy-nonenal, oxidized phosphatidylcholine, and isoprostanes in patients diagnosed with MS compared to controls [ 13 , 32 , 33 , 34 , 35 , 37 , 38 , 39 , 40 , 45 , 46 , 47 ], with some exceptions [ 36 ]. CSF levels of certain prostaglandins were increased in patients with MS in most studies [ 35 ,…”
Section: Oxidative Stress Markers In Patients With Multiple Sclerosismentioning
confidence: 99%
“…The CSF human serum albumin (HAS), mercaptoalbumin (HMA), and non-mercaptoalbumins 1 and 2 (HNA1 and HNA2) [ 65 ] levels were reported to be similar in MS patients and controls. CSF neutrophil gelatinase-associated lipocalin (NGAL) was increased [ 39 ] or similar [ 38 ] compared to controls in two studies by the same group. Finally, DJ-1 [ 66 ], periredoxins 2 (PRX2) [ 38 , 39 ], and β-site amyloid precursor protein-cleaving enzyme 1 (BACE1) [ 67 ] were increased in the CSF of patients with MS compared to controls.…”
Section: Oxidative Stress Markers In Patients With Multiple Sclerosismentioning
confidence: 99%
See 1 more Smart Citation

Oxidative Stress Markers in Multiple Sclerosis

Jiménez-Jiménez,
Alonso-Navarro,
Salgado-Cámara
et al. 2024
IJMS